The Effect of Intravitreal Injection of Erythropoietin in Treatment of Nonarteritic Anterior Ischemic Optic Neuropathy - Alireza Dehghani; Heshmatollah Ghanbari; Mehdi Kamani; Mehdi Raie (مجله دانشکده پزشکی اصفهان, 2017)
Background: Nonarteritic anterior ischemic optic neuropathy (NA-AION) is a disease with serious complications that already does not have any standard treatment. Some studies and experiences had shown that intravitreal erythropoietin injection has a neuroprotective effect. But there are some different and inconsistent results in those studies. So, the aim of this study was determining the effect of intravitreal injection of erythropoietin in treatment of the disease.